1990
DOI: 10.1002/1097-4679(199011)46:6<755::aid-jclp2270460609>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Detection of deception on the millon clinical multiaxial inventory (MCMI)

Abstract: Subjects from a correctional inmate (94 incarcerated males with no history of psychiatric treatment) and a forensic inpatient (144 males and 7 females) setting were divided into distorted and nondistorted groups based on “fake bad” instructions and concurrent MMPI profiles. All subjects also were administered the MCMI. Significant differences were found between groups for MCMI profile validity, weight factor scores, and total profile correction scores. MCMI profiles were consistent with expected symptomatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…(Millon, 1987, p. 116). Nonetheless, both the DIS and the DEB have been studied as potentially useful in the evaluation of malingering (e.g., McNiel & Meyer, 1990).…”
Section: Dis Scalementioning
confidence: 99%
“…(Millon, 1987, p. 116). Nonetheless, both the DIS and the DEB have been studied as potentially useful in the evaluation of malingering (e.g., McNiel & Meyer, 1990).…”
Section: Dis Scalementioning
confidence: 99%
“…The test was sensitive to both acute clinical distress and to the antisocial and narcissistic features that are so prevalent in correctional settings (Langevin et al, 1988;McNeil & Meyer, 1990). Zarella, Schuerger, and Ritz (1990) found significant associations between MCMI scales and MMPI subscales and personality disorder scales within a correctional setting.…”
mentioning
confidence: 97%
“…Wierzbici and Howard (1992) found that inmates with higher educational levels and intelligence showed a greater tendency to avoid the obvious items on the test, though the subtle-obvious distinction may not be important because little difference appears when subjects are asked to fake good or answer honestly (Peterson, Clark, & Bennet, 1989). The test was sensitive to both acute clinical distress and to the antisocial and narcissistic features that are so prevalent in correctional settings (Langevin et al, 1988;McNeil & Meyer, 1990). Zarella, Schuerger, and Ritz (1990) found significant associations between MCMI scales and MMPI subscales and personality disorder scales within a correctional setting.…”
mentioning
confidence: 97%
“…Compared with all other participants, those who failed neuropsychological SVTs had higher scores on many MCMI personality disorder scales, as well as the Alcohol Abuse, Psychotic Thinking, and Psychotic Depression clinical scales. These findings ought to be interpreted with some caution, however, as the diagnostic efficiency of the original MCMI personality and clinical scales is questionable (Choca, 2004), the use of a weight factor for classification of psychiatric malingering has not been sufficiently examined (e.g., McNiel & Meyer, 1990;van Gorp & Meyer, 1986), and the Rey-15 has been shown to have only moderate sensitivity as a measure of neuropsychological malingering (Vickery, Berry, Inman, Harris, & Orey, 2001). Nonetheless, this investigation is the first to suggest a potential dissociation between exaggerated symptoms of severe psychopathology and neuropsychological malingering using the MCMI.…”
mentioning
confidence: 99%